WP1-23 Vascular collagen 4A1 in subcortical white matter of older people and primates. Issue 3 (14th February 2019) - Shtaya, A; Yeo, NE; Whittaker, M; Pereira, E; Bridges, LR; Zamboni, G; Esiri, MM; Farris, CW; Rosene, DL; Hainsworth, AH
Abstract : Objectives: To test whether collagen 4A1 in cerebral small arteries associated with age, hypertension or small vessel disease (SVD). Design: Neuropathology cohort study. Subjects: Older people age >65 years with minimal Alzheimer's Disease. Methods: We examined subcortical white matter in archived brain tissue from older people (n=34, 15F/19M, median age 84, range 65–99 y) and from experimental non-human primates (NHP, Macaca mulatta) that were young adults (n=9, age 6.2–8.3 y) or older adults (n=8, age 17.0–22.7 y). Some of the primates (5 young, 3 older) were chronically hypertensive. Vascular collagen 4A1 immunohistochemical labelling was examined qualitatively and quantified as percent area fraction. Results: Collagen 4A1 labelling was common in arterial myocytes and in the adventitial layer in human and primate brain arteries, as well as in basement membrane, which frequently exhibited replication. Among older people, collagen 4A1 associated with neuropathological SVD severity (sclerotic index; r=−0.461, p=0.0409, least squares) and with radiological SVD severity (leukoaraiosis; p=0.0455, 1-way ANOVA) but not with age or clinical history of hypertension. In NHP, age but not hypertension was significantly associated with collagen-4A1 labelling (p=0.0396, 0.232 respectively, 2-way ANOVA). Conclusions: In this small cohort, vascular collagen 4A1 was related to SVD severity in older humans, in accord with genetic associations of COL4A1 with SVD phenotypes.